P53-Dependent apoptosis induced in human bronchial epithelial (16-HBE) cells by PM2.5 sampled from air in Guangzhou, China. (20th October 2014) - Zhou, Bo; Liang, Guiqiang; Qin, Huiyan; Peng, Xiaowu; Huang, Jiongli; Li, Qin; Qing, Li; Zhang, Li'e; Chen, Li; Ye, Li; Niu, Piye; Zou, Yunfeng
Abstract: Epidemiological studies have shown that air pollution particulate matter (PM) is associated with increased respiratory morbidity and mortality. However, the mechanisms are not fully understood. Oxidative stress-mediated apoptosis plays an important role in the occurrence of respiratory diseases. In this study, human bronchial epithelial (16-HBE) cells were exposed to different concentrations (16–128 µg/ml) of PM2.5 for 24 h to investigate the apoptosis induced by PM2.5 . The results showed that PM2.5 exposure significantly induced apoptosis, DNA strand breaks, and oxidative damage in a dose-dependent manner in 16-HBE cells. The expression of p53 and p73 increased significantly along with the dose of PM2.5 in 16-HBE cells, whereas the expression of p21 Cip1/WAF1 decreased; the expression of mdm2 increased and then decreased, but not significantly. Taken together, these observations indicate that PM2.5 may lead to oxidative damage and induce apoptosis through the p53-dependent pathway in 16-HBE cells. p53-dependent apoptosis mediated by DNA strand breaks may be an important mechanism of PM2.5 -induced apoptosis in 16-HBE cells.